PSI-Toolkit–an Extensible and Tightly Integrated Set of NLP Tools - Junczys-Dowmunt, Marcin; al, et (2009)
The paper reports on PSI—Toolkit, an extensible set of NLP tools developed at Adam Mickiewicz University in Poznan. All processors of the toolkit operate on a common data structure called PSI-lattice. This feature allows the seamless incorporation of NLP tools created by other researchers. PSI-Toolkit is licensed under LGPL, which allows for unrestricted commercial use.